(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Alla ricerca del popolo - 2. Il popolo politico - 3. Il popolo religioso - 4. L’intreccio populistico ereditato - 5. L’intreccio populistico in atto - 6. L’assalto dell’anti-pluralismo - 7. L’antidoto della laicità. Populism, Religions, Law ABSTRACT – The political populism has a background that is not easily detectable: the sense of religious or the sacred that enlivens the holistic view, without intermediate groups, of the people. The political populism needs symbols and goes to the ancient religious image. This tissue is looming on the law plan because aims to break up the fundamentals principles of the constitutional state, particularly the citizens equality according to their cultures and identities. To counter the innate antipluralism of the populism there soars the principle of secularism with its content of respect for the differences and, under this point of view, limit of the popular soveregnty.